TECHNOLOGICAL POTENTIAL OF APPLYING SILVER COFFEE FILM (Coffeasp.) AS A BIOFILM FOR THE CONSERVATION OF FRUITS AND VEGETABLES (REMUNOM, 2026)
Brasil, the world leader in coffee production, generates a significant volume of agro-industrial waste, with more than 50% of the coffee fruit mass being discarded during processing. One of the main by products is the coffee silverskin, a roasting residue with a high content of dietary fiber and rich in bioactive compounds, such as phenolic acids and flavonoids. These compounds have proven antioxidant capacity and functional properties that go beyond nutrition. In parallel, the fruit and vegetable sector faces post-harvest losses due to the high perishability of these foods. To reduce this waste, biodegradable biofilms emerge as a promising technology, acting as protective barriers that control the transfer of oxygen and moisture, thereby prolonging the shelf life of the products. Given the functional potential of coffee silverskin and the need for sustainable solutions for horticultural conservation, the present study proposes the use of coffee silverskin as a source of bioactive compounds for the enrichment of edible biofilms. This approach aims to fully utilize a residue from the coffee chain to develop an efficient and sustainable technology that contributes to the reduction of post-harvest losses.